Question
upstudy study bank question image url

For \( f(x)=x^{2}+6 \) and \( g(x)=\sqrt{5-x} \), find a. \( (f \circ g)(x) ; \quad \) b. the domain of \( f \circ g \)

Ask by Cummings Cole. in the United States
Feb 11,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a. \( (f \circ g)(x) = 11 - x \) b. The domain of \( f \circ g \) is all real numbers less than or equal to 5.

Solution

To solve the problem, we will follow these steps: 1. **Find \( (f \circ g)(x) \)**, which means we will substitute \( g(x) \) into \( f(x) \). 2. **Determine the domain of \( f \circ g \)** by considering the domain of \( g(x) \) and ensuring that the output of \( g(x) \) is within the domain of \( f(x) \). ### Step 1: Find \( (f \circ g)(x) \) The composition \( (f \circ g)(x) \) is defined as \( f(g(x)) \). Given: - \( f(x) = x^2 + 6 \) - \( g(x) = \sqrt{5 - x} \) Now, we substitute \( g(x) \) into \( f(x) \): \[ (f \circ g)(x) = f(g(x)) = f(\sqrt{5 - x}) = (\sqrt{5 - x})^2 + 6 \] Calculating this gives: \[ (f \circ g)(x) = 5 - x + 6 = 11 - x \] ### Step 2: Determine the domain of \( f \circ g \) To find the domain of \( f \circ g \), we need to consider the domain of \( g(x) \) first. The function \( g(x) = \sqrt{5 - x} \) is defined when the expression under the square root is non-negative: \[ 5 - x \geq 0 \implies x \leq 5 \] Thus, the domain of \( g(x) \) is \( (-\infty, 5] \). Next, we need to ensure that the output of \( g(x) \) is within the domain of \( f(x) \). The function \( f(x) = x^2 + 6 \) is defined for all real numbers, so there are no additional restrictions from \( f(x) \). Therefore, the domain of \( f \circ g \) is the same as the domain of \( g(x) \): \[ \text{Domain of } (f \circ g) = (-\infty, 5] \] ### Final Answers a. \( (f \circ g)(x) = 11 - x \) b. The domain of \( f \circ g \) is \( (-\infty, 5] \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find \( (f \circ g)(x) \), we first apply the function \( g \) to \( x \), and then substitute that result into \( f \). a. \( (f \circ g)(x) = f(g(x)) = f(\sqrt{5-x}) \). Now substitute \( g(x) \) into \( f \): \[ f(g(x)) = f(\sqrt{5-x}) = (\sqrt{5-x})^2 + 6 = 5 - x + 6 = 11 - x. \] So, \( (f \circ g)(x) = 11 - x \). b. To find the domain of \( f \circ g \), we need the output of \( g(x) \) to be valid input for \( f(x) \). Since \( g(x) = \sqrt{5 - x} \), its domain is \( x \leq 5 \) (as the expression under the square root cannot be negative). Additionally, \( 5 - x \) must be non-negative, which gives \( x \leq 5 \). As there are no additional restrictions from \( f(x) \), the domain of \( f \circ g \) is \( (-\infty, 5] \).

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy